Investigation of the relationship between intergranular corrosion and retrogression and reaging in the AA6063 - Ozer, Gokhan; Kisasoz, Alptekin; Karaaslan, Ahmet (WILEY-V C H VERLAG GMBH, 2019)
AA6063 was heat treated with different retrogression temperatures and durations, and the effect of heat treatment conditions on the microstructure, hardness, electrical conductivity, intergranular corrosion (IGC) and electrochemical corrosion behaviours of the AA6063 was determined compared with the T6 condition. The IGC test was applied according to the BS EN ISO 11846: 2008 standard. Moreover, potentiodynamic polarization tests were applied to determine the electrochemical corrosion behaviour of the heat-treated samples. Electrochemical corrosion tests were carried out by using a Ivium Compactstat potentiostat in 3.5 wt.%. NaCl solution at 24 degrees C with a scanning rate of 0.5 mV/s. The corrosion test cell consisted of the reference electrode (Ag/AgCl), working electrode (test sample) and a reference electrode (platinum). The effect of IGC on the microstructure of AA6063 and corrosion depth values was investigated by using a stereo optical microscope and a light metal microscope, respectively. Corrosion depth examinations were performed on microstructures taken from the cross-sections of the samples. The chemistry of the precipitates formed at grain boundaries and distribution of the precipitates in the microstructure were investigated by scanning electron microscope, energy dispersive X-ray and transmission electron microscope analyses. The results showed that retrogression and reaging heat treatment improves both the corrosion resistance and the mechanical properties of AA6063. After 50 degrees C/15 min RRA heat treatment, the highest corrosion resistance and a higher hardness value than the T6 level were obtained.
Keywords: AA6063; electrochemical corrosion; intergranular corrosion; retrogression and reaging; SERIES ALUMINUM-ALLOYS; MG-SI ALLOYS; HEAT-TREATMENT; COPPER CONTENT; CU CONTENT; PRECIPITATION; MICROSTRUCTURE; RESISTANCE; BEHAVIOR; RATIO; Materials Science; Metallurgy & Metallurgical Engineering